The Impact of Opportunity Management on the Relationship Business Model (A Study in the Polish Housing Industry) - Deszczy?ski, Bartosz (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
This paper illustrates the level of proficiency of multistage and multi-channel dialogue between the customers and the companies on the example of opportunity management conducted primarily in the Polish housing industry. Opportunity management (also called lead management) is an initial customer relationship management (CRM) process that connects the sales persons and the customers ready to make a purchase. Unlike the other processes its close link to transaction makes it ideal to achieve quick-wins making CRM business case cogent. However the research shows that the companies have severe problems in sustaining coherent dialogue with their prospective buyers what possibly reflects their relationship management immaturity. The aim of this article is to explain the nature of this phenomenon and its impact on the relationship business model.